Childhood maltreatment and emotion regulation in everyday life: an experience sampling study - Andrei Ion; Mirela I. Bîlc; Simina Pițur; Claudia Felicia Pop; Aurora Szentágotai-Tătar; Andrei C. Miu (Scientific Reports, 2023)
Abstract Childhood maltreatment is a major risk factor for psychopathology, and increasing evidence suggests that emotion regulation is one of the underlying mechanisms. However, most of this evidence comes from single assessments of habitual emotion regulation, which may not overlap with spontaneous emotion regulation in daily life and which fail to account for within-individual variability in emotion regulation across multiple contexts. In the present study, we investigated the relation between history of childhood maltreatment, positive and negative affect, and multiple dimensions of spontaneous emotion regulation (strategy use, emotion regulation goals, emotion regulation success and effort) in everyday life, using experience sampling method (3 assessments/day, for 10 consecutive days), in a sample of healthy volunteers (N = 118). Multilevel modeling results indicated that childhood maltreatment was associated with lower positive affect and higher negative affect. Childhood maltreatment was also related to lower use of reappraisal and savoring (but not suppression, rumination and distraction), reduced emotion regulation success (but not effort), as well as lower levels of and higher within-individual variability of hedonic (but not instrumental) emotion regulation goals. These results provide ecological evidence for multiple differences in emotion regulation in individuals with a history of childhood maltreatment.